Oyster Mushroom (Pleurotus ostreatus) Inhibits Migration and Metastasis on 4T1 Breast Cancer Cells - Lodyta Nawang Tika; Layung Sekar Sih Wikanthi; Shofa Annur; Retno Murwanti (Indonesian Society for Cancer Chemoprevention, 2016)
Metastasis is the main cause of death among brast cancer patient. Pleorotus ostreatus is known as anticancer agent that inhibits angiogenesis. Ethanolic extract of Pleorotus ostreatus (EEP) which contains lovastatin is predicted to inhibit metastatic cancer through inhibition of MMP-2 and MMP-9. The aim of this study was to determined antiproliferative and anti metastatic activity of EEPw (Ethanolic extract of wet Pleorotus ostreatus) and EEPd (Ethanolic extract of dried Pleorotus ostreatus ) in 4T1 metastatic breast cancer cells line. Qualitative analysis of lovastatin was determined by thin layer chromatography (TLC) using dicloromethan and etil acetat as mobile phase and lovastatin standard. Scratch wound healing assay was used to determine migration inhition ability of EEP while MMP-9 and MMP-2 activity were analysed by gelatine zymography. Molecular docking was performed to know the interaction between lovastatin and MMP-2 & MMP-9. The result showed that EEPw and EEPd contain lovastatin which were proved by spray reaction with anisaldehid. Each of EEPw and EPPd had cytotoxic activity with IC50 760 and 400 μg/mL respectively. Both of them inhibited closure for about 50 % on 4T1 metastatic breast cancer cells line compared to control. Either EEPw or EEPd decreased MMP-9 expression level compared to control. Lovastatin had higher affinity to bond with either MMP-2 or MMP-9 than native ligand. Overall, EEP could be developed as anticancer agent which was targeted on MMP-2 and MMP-9.Keywords : Pleurotus ostreatus, 4T1 metastatic cells, MMP-2, MMP-2, antimetastatic